STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENGHADAPI PANDEMIC COVID-19 - Ardian Arismunandar; Ahmad Faisal (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
At its core the COVID-19 pandemic is a human crisis. Thus, human resource (HR) leadershave been central to the response in organisations globally. This contrasts with previouscrises such as the global recession of 2008 through 2009 or the Y2K crisis at the turn of the millennium that accentuated the roles of finance and IT leaders, respectively. By amplifyingthe role of HR leaders, COVID-19 has become an inflection point with substantiveimplications for HR globally. In this commentary, we reflect on the implicationsof COVID-19 for HR research, including identifying some key research questions for strategic humanresource management (HRM).This narrow focus limits our understanding of key questions exposed during COVID-19. For example, the pandemic requires a shift in understanding of how work context, such asworking onsite versus working from home (WFH), influences employee behaviours and actions. The pandemic has also exposed tensions among stakeholders and challenges the primacy of the shareholder view which has dominated thinking in strategic HRM.The method used in this research is literature review. The research results note that whileHR has taken strategic steps, the tensions surrounding its role have come to light during thepandemic, highlighting the requirements for both strategic and tactical contributions